Buddhist statecraft in East Asia - Balkwill, Stephanie; Benn, James A. (Studies on East Asian religions, 2022)
Introduction / Stephanie Balkwill and James Benn -- 1. Metropolitan Buddhism vis-à-vis Buddhism at the Metropolis: How to Understand the Ling in the Empress Dowager's Name / Stephanie Balkwill -- 2. Silla King Chinhŭng Institutes State-Protection Buddhist Rituals / Richard D. McBride II -- 3. The Commissioner of Merit and Virtue: Buddhism and the Tang Central Government / Geoffrey C. Goble -- 4. Images of Humane Kings: Rulers in the Dali-Kingdom Painting of Buddhist Images / Megan Bryson -- 5. Buddhism and Statecraft in Korea: The Long View / Gregory N. Evon -- 6. Refusing the Ruler's Offerings: Accommodation and Martyrdom in Early Modern Nichiren Buddhism / Jacqueline I. Stone -- Index.